(3OjhGf LYaQ GdgQs - (3LYaQ GdgQ GdMGFQj,J (B1347 (3g` s
(3ChdgG (B:s
(3eHJhQ hChd GdehLhO efg(B: (3YGOdj YjO GdJgGfj hGdg````fG hMHjHj RGQfj HYO GdUOhO hUaG dj Uah ENhGf GdUaG HYO gLQ hUOhO hLaG s
(3BNQgG (B:s
(3ef bUjOI aj eOM LfGH GdTjN eMeO fLd GdeQMhe Rjf GdYGHOjf BNQgG(B: (3Ef Jcf Yf eOMce bGU```QI bO HdZJe ef dOf ehSi EYJPGQG s
(3jdj GdOjhGf eLehYI bUGFO GdTYQGA oeNJdajf ef hQbI (B28-37s
(3hGdOjhGf ZjQ oeQJH Ydi GdbhGajs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B68 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeYI GdchaI (B- (3HZOGO (B(130) s
Keywords: (3GdCOHs